2021
DOI: 10.1038/s41598-021-01303-5
|View full text |Cite
|
Sign up to set email alerts
|

A novel strategy for comprehensive optimization of structural and operational parameters in a supersonic separator using computational fluid dynamics modeling

Abstract: In this study, the effects of several structural and operational parameters affecting the separation efficiency of supersonic separators were investigated by numerical methods. Different turbulence models were used and their accuracies were evaluated. Based on the error analysis, the V2-f turbulence model was more accurate for describing the high swirling turbulent flow than other investigated turbulence models. Therefore, the V2-f turbulence model and particle tracing model were selected to optimize the struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 42 publications
(52 reference statements)
0
12
0
Order By: Relevance
“…For the assumption that the flow velocity at the downstream valve orifice is the speed of sound in the mass-flow-rate characterization parameters measurement method of HPSVs, the CFD method was used to study the gas flow through the two valve orifices 26 . CFD is known as a robust method for predicting fluid dynamics parameters and the most common software is ANSYS/fluent 27 , 28 . As shown in Fig.…”
Section: Principle Of Measurement Of the Mass-flow-rate Characterizat...mentioning
confidence: 99%
“…For the assumption that the flow velocity at the downstream valve orifice is the speed of sound in the mass-flow-rate characterization parameters measurement method of HPSVs, the CFD method was used to study the gas flow through the two valve orifices 26 . CFD is known as a robust method for predicting fluid dynamics parameters and the most common software is ANSYS/fluent 27 , 28 . As shown in Fig.…”
Section: Principle Of Measurement Of the Mass-flow-rate Characterizat...mentioning
confidence: 99%
“…Three main refrigeration processes include Joule–Thomson (JT) process, turbo-expander process and 3S process 3 . The JT process is the most common liquefaction process in the natural gas industry, however, based on the results the separation efficiency of 3S is higher than JT process 3 , 7 . Alfyorov et al 17 reported this converging–diverging nozzle separates the natural gas species with up to about 20% saving in compressor energy consumption compared to the same operational condition conducted by the JT valve and Turbo-expander.…”
Section: Introductionmentioning
confidence: 97%
“…In recent years, a significant part of the studies have been done to optimize the thermal efficiency of various processes 3 , 7 9 . Process simulations and numerical studies are generally used for these optimizations 4 , 10 12 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations